IbM BAGI KELOMPOK PENGRAJIN GERABAH DUSUN PAGERJURANG KLATEN SEBAGAI UPAYA MENINGKATKAN KAPABILITAS USAHA - Dewanti, Ida Susi; Suprapto, Adi; Susanta, - (Universitas Negeri Yogyakarta, 2016)
Lack of knowledge and skills in product development making traditional potteryartisans in the village Pagerjurang not been able to increase the economic value of the products. While the potential of pottery in the village is very large, plus a slanted rotary tool which is the cultural heritage of the ancestors and the only one in Indonesia. On the other hand, the modern pottery craftsmen in this village already capable of making pottery as a work of art with a high economic value that integrates traditional pottery art with batik skills, which were developed are batik ornament, but have limited business capabilities to meet market demand. This IbM activities lead to create synergies between traditional and modern pottery craftsmen, so as to improve the business capabilities of both groups of the pottery craftsmen. The method used is the business couching, training, and knowledge and technology transfer. The results of the IbM implementation able to help artisans modern expand its production apacity, craftsmen traditional pottery has led to the innovation of making pottery with batik ornaments, artisan pottery capable of calculating production cost and selling prices. Other than that IbM team give the oven test of glaciers and batik for media pottery tools